School Teachers and Soft Decolonisation in Dutch–Indonesian Relations, 1945–1949 - Suwignyo, Agus (Cambridge University Press, 2021)
The emergence of two states in Indonesia in the aftermath of the Second World War, namely the Republic of Indonesia and the Netherlands Indies Civil Administration, instigated a war that imposed citizenship, which schoolteachers had to choose carefully. By examining the quest for professional trajectories of Dutch and Indonesian schoolteachers during the 1945–1949 period, this paper argues that expanding citizenship fostered decolonisation through the teachers’ detachment from a shared dream of social mobility. The post–World War II reconstruction project, which is largely depicted as narratives of state building in many of the existing bibliographies, reflected a growing discontent in teachers’ expectations for economic reestablishment at the personal levels. The teachers’ detachment from a shared dream of social mobility reflected the dissolution of an imagined community where transnational cultural identities had met and melded in the early twentieth century. In contrast to the emerging historiography that emphasises atrocities and violence, this paper offers a perspective on the soft process of decolonisation